Sudden Cardiac Death and Catecholaminergic Polymorphic Ventricular Tachycardia: What Genetic Medicine could offer - Bhuiyan, Zahurul A (Cardiovascular Journal, 2021)
Abstract not available Cardiovasc. j. 2021; 13(2): 106-111